Sistem Informasi Inventarisasi Aset Berbasis Web GIS di PT. PLN (Persero) Sektor Pembangkitan Tarahan - Rangga Firdaus; Kurnia Muludi; Saur Pangihutan Sinurat (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
Asset management is very important aspect to company like PT. PLN. Asset management may include record keeping, maintenance and environment management. Recording information asset owned by a company is the primary and most important thing to do. With the information obtained from the recording of data asset, the company will be able to know exactly what asset and how exactly the asset owned by the company. Having recorded assets, the company will be able to optimize the use of assets and the company will be easier to undertake further asset management. PT PLN (Persero) Tarahan’s Generating Sector is a Steam Power Plant which has assets spread both inside and outside the building. The dominant’s equipmens in this site plant are the generating engines. The process of recording information of assets in PT PLN (Persero) Tarahan’s Generating Sector is not entirely managed by computerized system. The process of recording assets is still done manually and not reliable. This research develoved an Asset Inventory Information System which has features that can do registration of information detail about attributes and monitoring and mapping the location of existing asset. This research is covering the fixed assets that exist in the Utility Building. Web-based GIS of Asset Inventory Information System is built by using MapServer and Pmapper. Pmapper is a framework based on MapServer and PHP/Mapscript. Pmapper provides a good set of tools ready to use and it has a plugin API to add functionalities. The toughness of this framework is able to run well in various web-browser. The aplication is expected to facilitate the company determine and monitor, hence its use can be optimized. Keywords : Asset Management, Fixed Asset, Asset Inventory, Pmapper, MapServer, Web-GIS, PLN.